Readability of Online Materials Related to Vocal Cord Leukoplakia. Issue 3 (August 2021) - Shneyderman, Matthew; Snow, Grace E.; Davis, Ruth; Best, Simon; Akst, Lee M.
Objectives: To assess readability and understandability of online materials for vocal cord leukoplakia. Study Design: Review of online materials. Setting: Academic medical center. Methods: A Google search of "vocal cord leukoplakia" was performed, and the first 50 websites were considered for analysis. Readability was measured by the Flesch Reading Ease Score (FRES), Flesch-Kincaid Grade Level (FKGL), and Simple Measure of Gobbledygook (SMOG). Understandability and actionability were assessed by 2 independent reviewers with the PEMAT-P (Patient Education Materials Assessment Tool for Printable Materials). Unpaired t tests compared scores between sites aimed at physicians and those at patients, and a Cohen's kappa was calculated to measure interrater reliability. Results: Twenty-two websites (17 patient oriented, 5 physician oriented) met inclusion criteria. For the entire cohort, FRES, FKGL, and SMOG scores (mean ± SD) were 36.90 ± 20.65, 12.96 ± 3.28, and 15.65 ± 3.57, respectively, indicating that materials were difficult to read at a >12th-grade level. PEMAT-P understandability and actionability scores were 73.65% ± 7.05% and 13.63% ± 22.47%. Statistically, patient-oriented sites were more easily read than physician-oriented sites ( P < .02 for each of the FRES, FKGL, and SMOG comparisons); there were no differences in understandability or actionability scores between these categories of sites. Conclusion: Online materials for vocal cord leukoplakia are written at a level more advanced than what is recommended for patient education materials. Awareness of the current ways that these online materials are failing our patients may lead to improved education materials in the future.